PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS ANDROID TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Tasya Safa Melinda; Nurashri Partasiwi; Arinta Rara Kirana (Epsilon: Jurnal Pendidikan Matematika, 2022)
The problem in this study is the low ability of students' mathematical communication in learning. The purpose of this study was to determine the effect of using android-based learning media on the mathematical communication abilities of Class VIII students in Odd Semesters of SMP Negeri 13 Bandar Lampung in the Academic Year 2022/2023. This study used an experimental method with the population in this study, namely all students in class VIII Odd Semester SMP Negeri 13 Bandar Lampung. The samples used in this study were two classes, namely class VIII-4 as the experimental class, and class VIII-3 as the control class. Samples were taken using the Cluster Random Sampling technique. To find out students' mathematical communication skills, a test was carried out in the form of an essay of five questions which had previously been tested for validity and reliability. Hypothesis testing in this study uses the t_hit formula. From the results of testing the hypothesis using the t_hit statistical formula, the value of t_hit = 4.04 is obtained. From the t distribution table at a significant level of 5% it is known that t_daf = 1.67, then t_hit>t_daf, which means that the average mathematical communication ability of students using Android-based learning media is higher than the average mathematical communication ability of students using conventional approaches.